2001
DOI: 10.1038/ng721
|View full text |Cite
|
Sign up to set email alerts
|

Wildtype Kras2 can inhibit lung carcinogenesis in mice

Abstract: Although the ras genes have long been established as proto-oncogenes, the dominant role of activated ras in cell transformation has been questioned. Previous studies have shown frequent loss of the wildtype Kras2 allele in both mouse and human lung adenocarcinomas. To address the possible tumor suppressor role of wildtype Kras2 in lung tumorigenesis, we have carried out a lung tumor bioassay in heterozygous Kras2-deficient mice. Mice with a heterozygous Kras2 deficiency were highly susceptible to the chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
240
2
3

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 280 publications
(267 citation statements)
references
References 41 publications
21
240
2
3
Order By: Relevance
“…37,38 Spandidos et al 39 observed that the normal Hras allele could have some suppressive role over the Hras oncogene. In fact, it has been shown that wild-type Kras2 itself has tumor suppressor activity over the Kras2 oncogene, 40 and we have shown that the Nras protooncogene can inhibit malignant properties in the presence of its oncogene. 41 All these findings strongly suggest that the normal ras allele could have some suppressive role in the transformation process by the oncogenic allele.…”
mentioning
confidence: 76%
“…37,38 Spandidos et al 39 observed that the normal Hras allele could have some suppressive role over the Hras oncogene. In fact, it has been shown that wild-type Kras2 itself has tumor suppressor activity over the Kras2 oncogene, 40 and we have shown that the Nras protooncogene can inhibit malignant properties in the presence of its oncogene. 41 All these findings strongly suggest that the normal ras allele could have some suppressive role in the transformation process by the oncogenic allele.…”
mentioning
confidence: 76%
“…We speculate that KLF4 is also a mediator of transforming growth factor-β (TGFβ)-p21 and adenomatosis polyposis coli (APC)-p21 signalling, thereby relaying signals elicited by multiple key tumour-suppressor pathways. 129 . The tumours, which suffer from a KRas mutation, often showed a loss of the remaining wild-type allele.…”
Section: Linking Opposing Forces In Cancermentioning
confidence: 99%
“…A total of 80 Ag protein/lane was loaded on a 15% SDS-PAGE gel and analyzed by Western blotting with anti-ERK antibody or anti-phospho-ERK antibody (Sigma Chemical) as described previously (33).…”
Section: Western Blot Analysis Of Erk Activitymentioning
confidence: 99%